The Effect Of Work Experience, Profesionalism And Remote Audit On Audit Quality - Bertha Elvy Napitupulu; Sita Dewi; Anthony Wijaya (International Journal of Informatics, Economics, Management and Science (IJIEMS), 2023)
Audit results are said to be of high quality if they have implemented several criteria including auditing standards and quality control standar. Audit quality is influenced by several factors including auditor work experience, auditor professionalism and audit process. Auditor work experience is an impotant thing for auditors because without high experience an auditor will be less effective in carrying out their duties and it will be difficult to adapt to their circumstances and situations that will be faced. The longer of the working hours and experience of the audtor give a better audit quality. Experinced auditors are more skilled and competent in their work. Professionalism is needed by an auditor to determine audit quality. To support professionalism, the auditor is carrying out his audit duties must guided by the audit standars set by the Indonesian Institue of Certified Public Accountants. Auditors with high professionalism will carry out audits appropriately and complete each stage of the audit process completely, taking into account inadequate audit evidence found during the audit process to produce a good audit quality. Due to social distancing, the audit process during the Covid-19 pandemic was carried out remotely by using information and communication technology. This audit process called a remote audit process or remote audit. The remote audit process allows auditors to work remotely which meands increasing efficiency and scope and maintining audit quality. However there are still obstacles in the use of remote auditing, including auditor skills and the absence of laws governing in the use of information technology in auditing. The purpose of this study was to determine the effect of work experince, professionalism, and remote audit on audit quality at Public Accounting Firm in DKI Jakarta. The sample is 100 auditors. Data analysis using Least Square/PLS Partial Analysis. The result of this research is that work experience and professionalism have an effect of audit quality. But remote audit has no effect on audit quality. There is a significant positive effect between work experience and professionalsm with audit quality.